Sistem Monitoring Perangkat Jaringan Menggunakan Protokol SNMP Dengan Notifikasi Email - Herman Kuswanto (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Abstract  –  The use of computer network today is very important in support of all the work, in this research made a network device monitoring system using SNMP protocol with email notification, from the test results use Nagios application can provide information about the problem on the network device in the form of notification setatus from device whether down or up, notification status will be displayed on Nagios web interface and notification also sent to email. Implementation of network monitoring system is very helpful in monitoring all existing network devices, so as to facilitate the network manager in detecting disturbances on the network quickly. Key Word: SNMP, Nagios, Network Monitoring